2017
DOI: 10.1136/tobaccocontrol-2016-053434
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to cigarette prices by different racial/ethnic groups of US adults

Abstract: ObjectiveTo evaluate the impact of cigarette prices on adult smoking for four US racial/ethnic groups: whites, African–Americans, Asians and Hispanics.MethodsWe analysed pooled cross-sectional data from the 2006/2007 and 2010/2011 Tobacco Use Supplement to the Current Population Survey (n=339 921 adults aged 18+) and cigarette price data from the Tax Burden on Tobacco. Using a two-part econometric model of cigarette demand that controlled for sociodemographic characteristics, state-level antismoking sentiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
1
21
2
Order By: Relevance
“…Results from the present study suggest that for certain groups (i.e., Hispanic and non-Hispanic White smokers), increasing tobacco excise taxation may only be associated with greater cessation treatment utilization when increased to the very highest taxation levels. These results are partially consistent with the results of Yao and colleagues (40) and Farrelly and colleagues (41) who found that, although all racial/ethnic groups reduce cigarette consumption in response to cigarette price increases, Hispanic smokers (40) and White smokers (41) may be less price-responsive than other racial/ethnic groups. Thus, for certain racial/ethnic groups, tobacco price increases may need to be of a greater magnitude in order to promote cessation treatment utilization.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the present study suggest that for certain groups (i.e., Hispanic and non-Hispanic White smokers), increasing tobacco excise taxation may only be associated with greater cessation treatment utilization when increased to the very highest taxation levels. These results are partially consistent with the results of Yao and colleagues (40) and Farrelly and colleagues (41) who found that, although all racial/ethnic groups reduce cigarette consumption in response to cigarette price increases, Hispanic smokers (40) and White smokers (41) may be less price-responsive than other racial/ethnic groups. Thus, for certain racial/ethnic groups, tobacco price increases may need to be of a greater magnitude in order to promote cessation treatment utilization.…”
Section: Discussionsupporting
confidence: 90%
“…We included in the analysis model sociodemographic characteristics that have shown associations with smoking behaviours, such as age groups (19–24, 25–34, 35–44, 45–54, 55–64 and 65 or more), sex (male, female), marital status (married, unmarried), educational attainment (less than high school, high school, some college or more) and income levels 10 20. Individual income levels were measured based on equivalised disposable income which was calculated by dividing the reported disposable household income by the square root of the number of household members 21.…”
Section: Methodsmentioning
confidence: 99%
“…We created a smoking intensity variable (average number of cigarettes consumed per day) by multiplying the number of days participants smoked during the last 30 days by the number of cigarettes they usually smoked each day on their smoking days, and then dividing the product by 30. 31 Demographic characteristics (ie, age, gender, race/ethnicity, educational attainment, location) were obtained. Age was calculated based on self-reported date of birth.…”
Section: Methodsmentioning
confidence: 99%
“…We created a smoking intensity variable (average number of cigarettes consumed per day) by multiplying the number of days participants smoked during the last 30 days by the number of cigarettes they usually smoked each day on their smoking days, and then dividing the product by 30. 31…”
Section: Methodsmentioning
confidence: 99%